Evaluation of the relationship between thromboembolic risk score (CHA2DS2-VASc) and inflammation and coagulation markers in patients with non-valvular atrial fibrillation in emergency department. - Yaman, Fatih Nazmi; Civelek, Birol; Yavuz, Bunyamin; Yilmaz, Mustafa; Atescelik, Metin; Sahan, Mustafa; Goktekin, Mehmet Cagri (Allied Acad, 2016)
Objective: To evaluate the relationship between CHA(2)DS(2)-VASc score and inflammation and coagulation markers in patients admitted to Emergency Department (ED) with non-valvular Atrial Fibrillation (AF). Methods and Results: Eighty-four patients with non-valvular AF were included in the study. CHA(2)DS(2)-VASc scores were calculated for these patients. In addition, plasma levels of BNP, hs-CRP, CRP, vWF and D-dimer were measured. The relationship between CHA(2)DS(2)-VASc score and these parameters were evaluated. Eleven (13%) patients were considered to be at low-risk due to CHA(2)DS(2)-VASc score being<2 and 73 (87%) patients were considered to be at high risk due to CHA(2)DS(2)-VASc score being >= 2. The mean age of patients was 68 +/- 13 years and 50 (60%) of patients were male. Plasma BNP, hs-CRP, CRP, vWF and D-dimer levels were significantly higher in high-risk group. In addition, a significant positive correlation was found between CHA(2)DS(2)-VASc score and BNP (r=0.436, p<0.001), D-Dimer (r=0.356, p=0.003), hs-CRP (r=0.335, p=0.002), CRP (r=0,331, p=0.002), vWF (r=0.330, p=0.002) and patient age (r=0.573, p<0.001). Conclusion: It was found that BNP, hs-CRP, CRP, vWF and D-dimer levels increase significantly and that there is a positive correlation between CHA(2)DS(2)-VASc and these markers in high-risk patients with CHA(2)DS(2)-VASc score >= 2.
Keywords: Atrial fibrillation; BNP; CHA(2)DS(2)-VASc score; D-Dimer; hs-CRP; vWF